Un joli mouton tout rond, tout rond English: a pretty sheep fully round, fully round - Hamel Judith (Moncton New-Brunswick, Canada Bouton d'or Acadie, 2002)
a story about a gilr who loved to look at sheeps. Every morning when she goes to school, she passes by the field where one sheep catches her eyes, he is so round and fluffy.